Linear programming for production planning of flat panel display / Khaled Mohammed Hussein Al-Kuhali - Al-Kuhali, Khaled Mohammed Hussein (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
The underlying research aim is to develop models based on linear programming to assist in FPD production planning. The specific objectives of the research are given below ; to develop a linear programming model for aggregate FPD production, with the intention of reducing the total cost of production. This is achieved by adjusting decision variables such as production demand, workforce, inventory holding cost, inventory balance, etc ; to formulate a linear programming model with piecewise linear production cost functions. The idea is to convert the resultant linear programming objective function to a piecewise linear production cost function from nonlinear status ; to develop a linear programming model for material requirement planning (MRP I). This is so as to satisfy all demand conditions whilst minimizing the average inventory total cost.